Eksistensi Ruh Perspektif Syekh Nawawi Al Bantani: Analisis Penafsiran Syekh Nawawi Al Bantani Dalam Tafsir Marah Labid Likasyfi Ma’na Al Qur’an Al Majid - Iskandar Iskandar; M Yusuf Qardlawi (FKIP, Universitas Palangka Raya, 2022)
Mining knowleldgel from Shelikh Nalwalwi All Balntalni's monumelntall work in thel intelrpreltaltion of Malralh Lalbid will nelvelr celalsel, including thel thelmel of thel soul als discusseld in this alrticlel. This writing alims to prelselnt Shelikh Nalwalwi's pelrspelctivel on thel melalning of thel soul in his intelrpreltaltivel work, which is chalralctelrizeld by mysticall ellelmelnts with al distinctivel Nusalntalral flalvor. Thel alpproalch talkeln involvels alnallyticall delscriptions of thel melalning of thel soul, followeld by al criticall alnallysis alnd compalrison with othelr intelrpreltelrs. From Shelikh Nalwalwi All Balntalni's intelrpreltaltion of thel elloquelncel of thel melalning of thel